Thrombotic Primary Antiphospholipid Syndrome: the profile of antibody positivity in patients from North India. (8th October 2014) - Ahluwalia, Jasmina; Sreedharanunni, Sreejesh; Kumar, Narender; Masih, Joseph; Bose, Sunil Kumar; Varma, Neelam; Varma, Subhash; Singh, Surjit
Abstract: Aim: We evaluated the frequency of antiphospholipid antibody syndrome (APS) in patients presenting with thrombosis of various vascular beds from North India and report the antibody profiles encountered. Patients and methods: A retrospective analysis was performed on the laboratory results of aCL (anticardiolipin), aβ2 Gp1 (anti‐βeta‐2 glycoprotein 1) antibody and LAC (lupus anticoagulant) of 1222 consecutive patients referred to the coagulation laboratory work‐up for a hypercoagulable/thrombophilic state over a period of 4 years between 2009 and 2013. LAC was screened with dRVVT (diluted Russel Viper Venom Test) and KCT (Kaolin clotting time), and aCL and aβ2 Gp1 antibodies with commercial enzyme‐linked immunosorbent assy kits. Results: The current APS criteria was satisfied in 3.85% of all patients and 4.2% of pediatric patients with thrombosis. The venous circulation was more frequently affected (59.6%). Cerebral arterial and intra‐abdominal vein involvement was common. Transient antibody positivity was seen in 44 (3.6%) cases. aβ2 Gp1, aCL and LAC were positive in 95%, 54.5% and 23% of patients with APS, respectively, during the initial visit and 93.6%, 23% and 17%, respectively, during the follow‐up visit. Persistent triple positivity was seen in only three cases. At initial testing, positivity for both aCL and aβ2 Gp1 was the most frequent pattern (38% of cases). Conclusions: aβ2 Gp1 antibody was the commonest antibody that was persistently positive in patients with thrombosis. Triple positivity for all antibodies had the highest specificity and positive predictive value to diagnose APS in the first visit, whereas aβ2 Gp1 antibody had the highest sensitivity and negative predictive value.